Pengetahuan, Religiusitas, Budaya dan Kepercayaan dan Minat Muzakki Membayar Zakat di Kabupaten Pidie - Muhammad; Aliamin Aliamin; Ratna Mulyany (Politeknik Ganesha Medan, 2023)
This study aims to determine the effect of knowledge, religiosity, culture, and beliefs jointly and partially on muzakki's interest in paying zakat directly to mustahik and paying zakat directly to mustahik and paying zakat at Baitul Mal, Pidie Regency. This study's data analysis method uses multiple linear regression to overcome the influence of independent variables. The population in this study is muzakki, whose population pays zakat in Baitul Mal, Pidie Regency. The results of the study show that knowledge influences interest in paying zakat at Baitul Mal; Religiosity does not affect Interest in Paying at the Baitul Mal of Pidie Regency; Culture does not affect interest in paying zakat in Baitul Mal, Pidie district; and Trust influences interest in paying zakat in Baitul Mal, Pidie Regency.